Analysis of the Needs for Developing the Quality of Graduates: Efforts to Increase the Competence of Candidates for Bachelor of Education - Ansar Ansar; Andi Wahed (Journal of Educational Science and Technology (EST), 2022)
This study aims to analyze the quality development needs of Fakultas Ilmu Pendidikan, Universitas Negeri Makassar FIP UNM graduates, provides a comprehensive analysis of the results of the tracers study, which provides an overview of the university's employability in an effort to overcome the problem of the suitability of graduates' abilities and skills with the needs of the graduate user community. The approach used in this study is quantitative using survey methods to obtain alumni feedback to detect existing competency needs. Data collection techniques using online questionnaires through tracer studies. The research population is 1414 alumni of the last three years with a sample size of 869 by purposive sampling, namely alumni from August 2019 to April 2021 at FIP UNM. The descriptive analysis was used to generate results from the acquired quantitative data using frequency counts and percentage. The results obtained include; 1) The level of absorption of FIP UNM alumni is in the high category with fields of study that are very close to the field of work. Competencies of FIP UNM alumni are in the high and very high categories, including; ethics, expertise based on knowledge, use of information technology, communication, cooperation, and self-development. The relevance of the curriculum to the field of work of FIP UNM alumni which has an influence on large and very large categories, includes; lectures, internships, practicum, work, and discussion methods. 2) Aspects of alumni development that are needed by FIP UNM are English language skills and student involvement/participation in research and the use of demonstration methods in learning. 3) The challenge of alumni development that needs to be maintained and improved by FIP UNM is the competitiveness of alumni in obtaining jobs and entrepreneurship according to their fields of expertise.